Analysis of the relationship between demographic variables and risk tolerance score - Nobre, Liana Holanda; Macedo, Alvaro Fabiano Pereira de; Nobre, Fabio Chaves; Silva, Wesley Vieira (Revista de Administração da UFSM, 2017)
Behavioral Finance is a modern branch of financial theory that aims to incorporate psychological and sociological issues in the investigation of market anomalies and individual investor behavior. This research sought to assess which demographic variables can be used to classify decision makers regarding to risk tolerance level. The questionnaire was applied with 305 individuals and its structure was based of the work of Gava and Vieira (2006), Grable and Lyntton (2001) and the Survey of Consumer Finances (SCF). Risk tolerance level was measured in two ways: an observable variable, from the SCF, and a latent variable composed of three constructs that refer to some risk dimensions: risk as investment, comfort and experience at risk and speculative risk (GRABLE; LYNTTON, 2001). In the analysis of data, Confirmatory Factor Analysis (CFA) and variance analysis (ANOVA) were used. Results show that the greatest impact on risk tolerance among the analyzed dimensions was the dimension comfort and experience with risk; it presented the highest mean and the highest correlation with the risk tolerance score. Regarding to the demographic variables, the research shows that young, single and childless individuals tend to accept more risk in their investments. The income presented a nonlinear effect on the risk tolerance, but the more risk tolerant are those who are better able to withstand the possible losses arising from higher risk investments.